Tax Inspection – Unlawful Interference - Czudek, Damian (Public Governance, Administration and Finances Law Review, 2018)
This article focuses on the issue of options, respectively the scope of application of the tax authorities’ discretion in the use of available instruments to ensure the objective of tax administration, i.e. the correct identification and determination of the tax and its payment. The article is based on a case study of the decision of the Supreme Administrative Court of the Czech Republic.